Вплив цільнозернового борошна на якість і профіль текстури затяжного печива - Ковальова, Ліліана; Сова, Наталія Анатоліївна; Алієв, Ельчин Бахтияр огли; Кошулько, Віталій Сергійович; Kovaliova, Liliana; Sova, Nataliia; Aliiev, Elchyn; Koshulko, Vitalii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті обґрунтовано актуальність удосконалення рецептури затяжного печива в контексті зростання попиту на продукти раціонального харчування. Мета роботи – дослідження впливу рецептури печива затяжного з використанням цільнозернового пшеничного та спельтового борошна, у тому числі з чорнозерних сортів, на якісні показники й профіль текстури готових виробів. Дослідження проведено на п’яти зразках: контроль і чотири дослідні з повною заміною борошна на цільнозернове пшеничне, цільнозернове спельтове, чорнозерне цільнозернове пшеничне й чорнозерне цільнозернове спельтове. Установлено, що використання цільнозернових та особливо чорнозерних видів борошна зумовлює зниження світлоти готового печива та формування більш насиченого темного кольору, підвищення вмісту білка, клітковини й зольних речовин порівняно з контролем. Реологічні дослідження показали істотну модифікацію властивостей тіста. За сукупністю отриманих результатів найбільш перспективними визначено зразки на основі чорнозерного цільнозернового борошна пшениці та спельти. /// EN: The article substantiates the relevance of improving hard biscuit (semi-sweet biscuit) formulations in the context of growing consumer demand for balanced nutrition products enriched with dietary fiber and biologically active compounds. The aim of the study is to investigate the effect of hard biscuit formulations using whole grain wheat and spelt flours, including black-grain varieties, on the quality indicators and texture profile of the finished products. The scientific novelty of the study lies in establishing the patterns of changes in sensory, color, and rheological characteristics of hard biscuits when whole-grain flour from black-grain wheat and black-grain spelt is used as the main flour raw material, as well as in confirming the existence of a market niche for such products in Ukraine. The practical significance consists in the proposed formulation solutions and technological parameters for producing hard biscuits with enhanced nutritional and biological value, suitable for positioning as health-oriented products. The study was conducted on five samples: a control sample (standard “Maria” recipe) and four experimental samples with complete replacement of flour by whole wheat flour, whole spelt flour, black-grain whole wheat flour, and blackgrain whole spelt flour. Flour quality indicators (moisture content, quantity and quality of gluten), dough moisture parameters, sensory characteristics of finished products, color characteristics of flour, dough, and biscuits, as well as chemical composition (proteins, fats, fiber, ash) and rheological properties of dough and finished products were determined. It was found that the use of whole-grain and especially black-grain flours resulted in reduced lightness of the finished biscuits and the formation of a more intense dark color, as well as increased protein content (up to 13.6 %), fiber content (up to 2.0 %), and ash content (up to 1.8 %) compared with the control sample, confirming the enhanced nutritional and mineral value of the products. Rheological studies revealed significant modifications in dough properties: the control sample demonstrated the highest extensibility and deformation energy, whereas samples made from black-grain flour formed a stronger but less extensible structure. Based on the overall quality indicators and nutritional composition, samples produced from black-grain whole wheat and black-grain whole spelt flour (№ 4 and № 5) were identified as the most promising.
Effect of whole grain flour on the quality and texture profile of hard biscuits
Keywords: борошно цільнозернове; чорнозерна пшениця; чорнозерна спельта; печиво затяжне; рео- логічні властивості; whole grain flour; black-grain wheat; black-grain spelt; semi-sweet biscuit; rheological properties